Tourism and heritage attractions - Prentice, Richard (Richard C.) (London ; New York : Routledge, 1993)
Cultural and historical attractions are principal factors generating tourism trips and this has spurred the growth of a large heritage industry. However, the character and behaviour of heritage tourists and their social and economic impact on their destinations is as yet little understood. Richard Prentice presents a detailed analysis of heritage tourism by examining the way the benefits gained from visits to attractions are consumed. This exploration into the nature of the heritage 'product' calls into question the terminology used to define this aspect of the tourism industry, and Richard Prentice argues that it is all too easily regarded as a homogenous industry when in fact it covers diverse attractions which serve diverse tourism and leisure markets. A more sensitive approach to such questions as the promotion of these attractions, their retailing role, their sustainability and their educational impact is needed within the industry. The author shows that the demands of tourists, their socio-economic background and the decision-making processes involved all have implications for the management and marketing of tourism. He analyses the benefits that tourists seek when visiting heritage attractions and measures their reactions to the presentation of such sites, asking how informed tourists are and what sort of promotion they respond to. By setting up a model of the heritage user, he attempts to identify key features which should influence tourist operators seeking to understand the behaviour of their tourist visitor and respond effectively.
1. Tourists' demands for heritage consumption -- 2. The heterogeneity of the heritage product -- 3. The socio-demographic characteristics of tourists at heritage attractions -- 4. Tourist decision-making and heritage attractions -- 5. Tourist trip making and visits to heritage attractions -- 6. The promotion of heritage attractions to tourists -- 7. The retailing role of heritage attractions -- 8. Tourist disposition towards conservation and commitment to heritage -- 9. Tourist assessment of heritage presentation -- 10. Benefits gained by tourists from visiting heritage attractions -- 11. Conclusion: the heritage market place summarised
Includes bibliographical references (pages [235]-242) and index.
Keywords: Historic sites -- Conservation and restoration -- Great Britain; Cultural property -- Protection -- Great Britain; Historical museums -- Great Britain; Heritage tourism -- Great Britain